2018
DOI: 10.3892/or.2018.6682
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MMP9 as a novel key gene in mantle cell lymphoma based on bioinformatic analysis and design of cyclic peptides as MMP9 inhibitors based on molecular docking

Abstract: Mantle cell lymphoma (MCL) is an aggressive disease. MCL is associated with poor patient prognosis and limited survival. To identify key genes and explore targeting cyclic peptide inhibitors for the treatment of MCL, we downloaded two gene expression profiles (GSE32018 and GSE9327) from the Gene Expression Omnibus (GEO) database. We screened 84 differentially expressed genes (DEGs). Pathway analysis showed that DEMs were mainly enriched in the ‘Pathway in cancer’, ‘PI3K-Akt signaling pathway’, ‘Cytokine-cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…In molecular docking, the ligand binds to one or more amino acid residues with hydrogen bonds in the active pocket, and participates in the process of conformational changes and energy complementation. 29 The binding sites and binding score values can intuitively reflect the interaction and stability of the docking model. Here, we select the first 15 targets with higher DOF (except for receptors lacking the original ligand in the PDB) to construct protein receptors based on hub targets of PPI.…”
Section: Resultsmentioning
confidence: 99%
“…In molecular docking, the ligand binds to one or more amino acid residues with hydrogen bonds in the active pocket, and participates in the process of conformational changes and energy complementation. 29 The binding sites and binding score values can intuitively reflect the interaction and stability of the docking model. Here, we select the first 15 targets with higher DOF (except for receptors lacking the original ligand in the PDB) to construct protein receptors based on hub targets of PPI.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that these two pathways were enriched in DEGs both in the GSE32018 and GSE9327 datasets, which used normal and reactive lymph nodes as controls, respectively (22). This indicates that the enriched pathways in DEGs between tumor samples and controls might be a reason for the selection of targeted agents in MCL, such as bortezomib interfering with the NF-kappa B signaling pathway (1).…”
Section: Discussionmentioning
confidence: 98%
“…In the literature the proteolytic cleavage of E-cad was reported for a number of sheddases, including zinc-dependent matrix metalloproteinases (MMP-2, -3, -7, -9 and -14), members of the disintegrin family (adamalysin/ADAM-10 and−15), bacterial proteases gingipains (HRgpA, RgpB, and Kgp), B. fragilis toxin/fragilysin, cysteine cathepsins (B, L, and S), serine protease Kallikrein-7 (KLK7), plasmin serine protease, aspartic proteinases BACE1 and BACE2, and malaria parasite serine proteinases PfSUB2n, PfROM1, and PfROM 4 (Grabowska and Day, 2012). One possible candidate for E-cad cleavage during C. burnetii infections could be the human MMP-9, since: (i) MMP-9 levels were reported elevated in the sera of patients with endocarditis (Thuny et al, 2012), and patients with acute Q fever (Krajinović et al, 2012); (ii) its production was induced in PBMCs of healthy persons following in vitro exposure to C. burnetii ; (iii) MMP-9 SNP was found more frequently in patients with persistent Q fever (Jansen et al, 2017); and (iv) MMP-9 was recently identified as a key gene in mantle cell lymphoma (Yan et al, 2018). Experiments are under progress in our laboratory to investigate whether C. burnetii infection induces the activation of a human cellular protease from the sheddase family or if C. burnetii itself encodes for a sheddase.…”
Section: Discussionmentioning
confidence: 99%